2017
DOI: 10.1177/0003319717712118
|View full text |Cite
|
Sign up to set email alerts
|

The Comparison of Angiographic Scoring Systems With the Predictors of Atherosclerosis

Abstract: Syntax score (SS) and Gensini score (GS) are used to determine the complexity and severity of coronary artery disease. Although there are some studies indicating the individual relationship of these scoring systems with the carotid intima-media thickness (cIMT) and epicardial fat tissue (EFT), there was no previous study that compared the SS and GS in that respect. We aimed to assess the relationship of SS and GS with predictors of atherosclerosis. We enrolled 522 patients. There were positive correlations bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 26 publications
0
12
0
1
Order By: Relevance
“…Previous studies also reported this correlation between carotid DUS results and the severity of coronary artery disease . Kalkan et al also showed that SXscore is significantly associated with carotid DUS findings, such as carotid intima‐media thickness. However, Avci et al favored that the Gensini score is well associated more with the severity of carotid disease than SXscore.…”
Section: Discussionmentioning
confidence: 63%
“…Previous studies also reported this correlation between carotid DUS results and the severity of coronary artery disease . Kalkan et al also showed that SXscore is significantly associated with carotid DUS findings, such as carotid intima‐media thickness. However, Avci et al favored that the Gensini score is well associated more with the severity of carotid disease than SXscore.…”
Section: Discussionmentioning
confidence: 63%
“…In patients with complex carotid plaques, complex coronary artery stenosis co-exists and the degree of the stenosis detected during the carotid artery Doppler examination and the stage of coronary artery disease correlate significantly [14][15][16][17]. Additionally, the SYNTAX score and intima-media thickness of carotid artery correlate significantly [18]. Akansel et al…”
Section: Discussionmentioning
confidence: 99%
“…The severity of coronary atherosclerosis is a key factor affecting the outcome of CAD. Currently, the severity and complexity of the obstructive coronary lesions in the clinic are often aggravated by the number of diseased vessels, as well as by various scoring systems (33). SYNTAX score is one of the quantitative tools used to measure the complexity of coronary artery lesions, as well as to guide optimal revascularization therapy in the clinic (34).…”
Section: Discussionmentioning
confidence: 99%